2001
DOI: 10.1310/yn11-xj4l-9yhf-19e4
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Immunological Response to HAART Therapy in a Community-Based Cohort of HIV-1-Positive Individuals

Abstract: The rate of virologic failure in this unselected group of patients was higher than that observed in randomized clinical trials, but only a minority (11%) of the patients were treatment naïve. Starting combination therapy simultaneously and initiating antiretroviral therapy before advanced HIV disease has developed predict virologic response, whereas the magnitude of viral suppression predicts mid to long immunological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
3
11
0
2
Order By: Relevance
“…Various studies, which compared NNRTI-and PIbased regimens as the initial treatment regimen, have reported that the virological response of patients under NNRTI-based treatment regimen is higher (9,10,(13)(14). Althogh the main factor for treatment failure has been reported to be resistance development in Europe and the USA, in the present study, treatment noncompliance was noted to be the main reason for treatment failure (10,11).…”
Section: Discussionsupporting
confidence: 51%
“…Various studies, which compared NNRTI-and PIbased regimens as the initial treatment regimen, have reported that the virological response of patients under NNRTI-based treatment regimen is higher (9,10,(13)(14). Althogh the main factor for treatment failure has been reported to be resistance development in Europe and the USA, in the present study, treatment noncompliance was noted to be the main reason for treatment failure (10,11).…”
Section: Discussionsupporting
confidence: 51%
“…Various randomized clinical trials (24)(25)(26)(27)(28)(29), have shown that 60%-90% of patients treated with HAART achieved sustained suppression of viral load below the detection limit of standard assays.…”
mentioning
confidence: 99%
“…In this study, with initial over all baseline mean CD4 count of 132.9 cells/mm 3 , showed a mean increase in CD4 count of 203.0 cells/mm 3 . Touloumi et al (24) showed that increase in CD4 cell counts is biphasic. It is believed that the initial rapid increase in CD4 cell counts is a result of the redistribution of trapped memory T cells into the peripheral blood from the lymph nodes together with a decrease in activation-induced apoptosis.…”
mentioning
confidence: 99%
“…Bu nedenle çalışmamızda 6., 12., 24. ve 48. ay kontrollerinin sonuçları değerlendirilmiştir. CD4 sayısının yüksek ve immünolojik durumunun daha iyi olduğu dönemde başlana-cak ART'nin hastanın mortalite ve morbiditesini azaltacağı düşünülmekte olup CD4 sayısı <200/ mm 3 iken ART başlanan olgularda AIDS'e ilerleme ve mortalitenin daha yüksek olduğu bildirilmektedir (4,9,10,12) . Etkin bir ART ile viral baskılanmayı takip eden haftalar içinde CD4 sayısının 50 hücre/ mm 3 'e yükselmesi beklenir.…”
Section: Gereç Ve Yöntemunclassified